Relapse and post-discharge body composition of children treated for acute malnutrition using a simplified, combined protocol: A nested cohort from the ComPAS RCT - Lelijveld, N; Musyoki, E; Adongo, SW; Mayberry, A; Wells, JC; Opondo, C; Kerac, M; Bailey, J (Public Library of Science, 2021)
Introduction Severe and moderate acute malnutrition (SAM and MAM) affect more than 50 million children worldwide yet 80% of these children do not access care. The Combined Protocol for Acute Malnutrition Study (ComPAS) trial assessed the effectiveness of a simplified, combined SAM/MAM protocol for children aged 6–59 months and found non-inferior recovery compared to standard care. To further inform policy, this study assessed post-discharge outcomes of children treated with this novel protocol in Kenya.